If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 78 = 6(7 + n) 78 = (7 * 6 + n * 6) 78 = (42 + 6n) Solving 78 = 42 + 6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation. 78 + -6n = 42 + 6n + -6n Combine like terms: 6n + -6n = 0 78 + -6n = 42 + 0 78 + -6n = 42 Add '-78' to each side of the equation. 78 + -78 + -6n = 42 + -78 Combine like terms: 78 + -78 = 0 0 + -6n = 42 + -78 -6n = 42 + -78 Combine like terms: 42 + -78 = -36 -6n = -36 Divide each side by '-6'. n = 6 Simplifying n = 6
| 3x+2=79.17 | | x^2+9x+14=-6 | | 3=-3(k-1) | | x^2-9x+14=-6 | | 11x+21=2x^2 | | 3+2x-(x-(-1))=2x+(-2)-(-x) | | -2f+-4=4 | | 7(5a-b)-6(2b-7a)= | | x^2-bx+27=0 | | 12=6(-8+n) | | 6y+2-5y^3=0 | | 5x-60=1440 | | -4(0.2x+0.3)-1.3=-0.1 | | x^2+9x+14=6 | | 2x^3-24x+32=0 | | -10-3x=50 | | 4x=6*12 | | 4x-60=1100 | | -4(-6)(-2)(1)= | | 4x-50=1200 | | 4x-50=600 | | 3p+2=-1 | | -2-v=-12 | | 2.1x=1.68 | | 4x-60=510 | | 2(3g+2)=12g+8 | | 0.05m-0.08m+m=0.97 | | 20=n+3 | | v-9=-7(v-1) | | 4x-60=300 | | -12z^5+10z^4+8z^3=0 | | 2(x+9)-10=34 |